Measuring, minimizing, and documenting the impact of onshore seismic surveys - Dean, Tim (2024)
Environmental approvals are a key part of acquiring a seismic survey. In this paper we describe a methodology that quantifies and then minimizes disturbance. Further environmental factors such as habitat fragmentation and predator-prey sight lines can also be taken into account along with safety related issues such as extreme topographical changes. The output of the process can be used directly as as evidence for environmental assessments.